Hubungan Permainan Game Online terhadap Gangguan Memori Pada Mahasiswa Fakultas Kedokteran Universitas Yarsi 2020 dan Tinjauannya Menurut Pandangan Islam - Tamrin, Andi Mohammad Arief; Prasetyo, Edi; Gunawan, Andri (Jurnal Ners, 2024)
This research aims to investigate the relationship between playing online games and memory impairment in YARSI University students class of 2020. This research uses quantitative methods with an analytical observational approach. The sample for this research was YARSI University medical students with a sample size of 74 population. The data collection process was carried out using the MMSE and MoCA – Ina questionnaires. The results of the research show that there is a significant relationship between playing online games and memory impairment with a degree of significance (a) = 0.05, so the probability is (?) = 0.015 < 0.05. The results of the study show that there is a significant relationship between playing online games and memory disorders in medical students at YARSI University 2020. This study concludes that there is a significant influence between the length of playing games on memory disorders, respondents with a high level of playing games tend to experience memory disorders. From an Islamic perspective, online games are permitted as long as they do not violate Islamic principles and values Keywords: Online Games, Memory, Islam.